Risk of guarantee, addication and restitution in sovereign sukuk: a case study of sukuk of state of cote d'ivoire sukuk = مخاطر الضمان، الاسترداد والتنازل في الصكوك السيادية: دراسة حالة صكوك كوديفوار - Zakariyah, Habeebullah; Lansine, Syllah (Usuli Faqih Research Centre PLT., 2020)
Recently, there have been notable trends in the Islamic financial industry in general and the sukuk industry particulary. Since then, many of the African, Western and Asians countries have issued Sukuk in their domestic and international financial market, because of economic benefits to both governments and the investors. In the light of this study, the article attempts to look at the extent the Sukuk of the state of Côte d'Ivoire whether or not was complied with the Islamic sovereign Sukuk norms and standards. Hence, in the purposes of studying these issues, the researcher puts focuses on the Cote d'Ivoire's Sukuk prospectus in studying shariah issues which some related to the contracts, agreements and the rights of investors which many countries failed to do so. In order to achieve this important study, the writer adopts analytical and explanatory method in data collection and evaluation, that with the use of contemporary Shar'iah standards. The research found out the shariah risk regarding the following matters the guarantee of investor's capital, such as the restitution of their right and the abdication of asset upon maturity. The study analyzes those issues based on the Islamic jurisprudential and scholarly thought. And the study stresses the need of reviewing the Sukuk structures to the aim in avoiding shariah violations that mostly resulting from the environment in which the sukuk are issued. **************************************************************************** شهدت الآونة الأخيرة توجها ملحوظا نحو الصناعة المالية الإسلامية بشكل عام وصناعة الصّكوك بوجه خاص. حيث قامت العديد من الدول الإفريقية، الغربية والآسبوية بإصدار صكوك في أسواقها المالية المحليّة والدّوليّة وذلك لما فيه من الفوائد الاقتصادية الرّاجعة على الحكومات والمستمثرين. ومن هذا المنطلق، تقوم هذه الدراسة بمحاولة تسليط الضّوء على مدى موافقة صكوك كوت ديفوار وانسجامها مع ضوابط ومعايير الصّكوك السّياديّة. وذلك بالتّركيز على أشرطة النّشرة ولوائحها وبيان القضايا الشّرعية والفقهية المتعلقة بالعقود والاتفاقيات والحقوق التي لم ينجح الكثير من إصدار الصّكوك منها. ولهذا الغرض، اعتمد الباحث في هذه الدّارسة على منهج التّحليل والاستقراء في جمع البيانات وتقييمها وذلك بالاعتماد على الكتب التّراثيّة والمؤلفات المعاصرة والمعايير الشّرعيّة. توصل البحث إلى بيان المخاطر الشّرعيّة التي تتعلق بضمان رأس مال المستثمرين أو التّنازل عن حقّهم حين الاستحقاق وكذلك مسألة الاسترداد. واستطاعت الدّارسة تحليل تلك المسائل بناء على الأقوال الفقهية. وأكّدت الدّراسة إلى حاجة هياكل الصّكوك إلى المراجعات والمتابعات الفقهية والشّرعيّة لهدف تفادي المخالفات الشّرعية النّاتجة عن البيئة التي تصدر فيها تلك الصّكوك.